KERJA SAMA INDONESIA DAN BELANDA MELALUI CAMDEN ASSET RECOVERY INTERAGENCY NETWORK (CARIN) DALAM PENGEMBALIAN ASET HASIL TINDAK PIDANA SIBER LINTAS NEGARA PADA TAHUN 2021 - Naudy Finomitya Fitrah Alyalira, (2023)
Asset recovery requires several steps or stages, including obtaining information or intelligence, gathering evidence, tracking assets, freezing and seizing assets, pursuing legal action, enforcing court orders or decisions, and finally turning assets over to the state. Due to the fact that transnational crimes often transcend national borders, it can be difficult for governments to pursue those responsible for committing them. This is because different countries have different laws which may not always be easy to implement. International agreements, such as Mutual Legal Assistant (MLA), which are the main type of international agreement used between countries as the basis for asset recovery agreements, are an important tool for achieving effective return on assets stemming from criminal activity from abroad. In practice, the implementation of MLA is still not optimal because the respondent country has the right to object. This research is focused on emphasizing the technical aspects of the implementation of cooperation that efforts can be carried out through informal channels. This research is the result of normative descriptive research carried out by means of literature studies and interviews with relevant informants. Based on the results of the author's research, apart from these provisions, there are several other international provisions contained in the United Nations Convention Against Corruption, 2003 which can be adopted and implemented in legislation to make asset recovery cooperation effective, one of which is through informal asset recovery networks. This study aims to find out about the mechanism of cooperation in returning assets resulting from cross-border cybercrime through the informal channel of the CARIN asset recovery network between Indonesia and the Netherlands in 2021